Cerebral Hyperperfusion Syndrome following Protected Carotid Artery Stenting - Rainer Knur (Case Reports in Vascular Medicine)
The cerebral hyperperfusion syndrome is a very rare complication after revascularization of the carotid artery and accompanied by postoperative or postinterventional hypertension in almost all patients. We report a case of a 77-year-old man who developed a complete aphasia and increased right-sided weakness following endovascular treatment of severe occlusive disease of the left internal carotid artery. We discuss the risk and management of cerebral hyperperfusion syndrome after carotid artery stenting.